3D cross-bended metasurfaces with polarization insensitivity and high-Q resonances. (8th September 2020) - Pan, Ruhao; Du, Shuo; Liu, Zhe; Zhu, Wei; Li, Ce; Gu, Changzhi; Li, Junjie
Abstract: Metasurfaces with high-quality (HQ) resonances are always desired for their potential applications in biomedicine and photonic devices. However, the realization of HQ near-infrared metasurfaces with polarization insensitivity has faced problems with metallic loss, large feature size and limited configurations. In order to build up HQ metasurfaces working at the near-infrared range, we propose a 3D bended metasurface configuration consisting of a metallic supported frame and cross vertical split ring resonators, which are fabricated by a focused ion beam defined origami method. The relationship between Q factor/modulation depth of the resonances and the geometric morphology of the meta-atoms are established, and its polarization insensitivity is verified. Two HQ resonances with 22%/26% modulation depth and the quality factor of 24/30 at 1.75/2.5 μ m are experimentally obtained in the optimized metasurface. In addition, a polarization insensitive Fano resonance with large modulation depth can also be observed at the low frequency band, which can be modulated by tuning the bending angle. This HQ 3D cross-bended metasurface will create a more flexible approach to design versatile micro/nano-photonic devices and biological components.